Analisis Yuridis Pertimbangan Hakim dalam Putusan Menolak atau Mengabulkan Izin Poligami di Pengadilan Agama Kota Palembang - Arza Amelia Tiara Putri; Khalisah Hayatuddin; Sofyan Hasan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Permission for polygamy is regulated in Law No. 1 of 1974 on Marriage, which affirms the principle of monogamy but provides for exceptions subject to obtaining permission from the court. This provision forms the basis for the examination of applications for permission for polygamy in the Palembang Religious Court. The results of the study show that in practice, judges do not only refer to the fulfilment of normative requirements as stipulated in laws and regulations, but also focus on sociological considerations, such as household conditions, the impact on wives and children, and aspects of public interest. A decision granting permission for polygamy provides legal legitimacy for the marriage to take place and creates new rights and obligations for the parties, while a decision to reject the application reinforces the principle of monogamy and serves as legal protection for the wife and children from potential injustice.